Altered quinidine disposition in a patient with chronic active hepatitis. Issue 676 (February 1982) - Powell, J. Robert; Conrad, Kenneth A.; Okada, Robert; Guentert, Theodor W.; Riegelman, Sidney
Abstract : A 49-year-old female with chronic active hepatitis and ventricular ectopic activity was given i.v. 600 mg quindine gluconate (4·4 mg/kg). Quinidine plasma concentrations were analysed by high pressure liquid chromatography and plasma protein binding by equilibrium dialysis. The pharmacokinetic values were total body clearance 0·11 l/kg/hr, elimination half-life 41·5 hr, volume of the central compartment 2·26 l/kg, volume of distribution from the area under the curve 6·5 l/kg, and 19% unbound in plasma. Based on the limited information available, quinidine dosing should be markedly decreased in patients with severe liver dysfunction.